Expert Review and Rasch Modelling of a Sustainability Awareness Instrument in the Context of Peatland Climate Realities under Global Warming Pressures - Lintang Auliya Kurdiati; Apit Fathurohman (Unnes Science Education Journal, 2025)
Sustainability awareness among students is crucial for fostering environmentally responsible behaviors, particularly concerning peatlands’ role in global warming. However, a valid and reliable measurement tool is needed to assess students’ awareness effectively. This study aims to examine the validity and reliability of a questionnaire designed to measure secondary school students’ sustainability awareness in this context. A descriptive survey design was employed, involving 40 participants eight expert validators and 32 students. Data were collected through expert validation and questionnaire distribution. Content validity was assessed by four content experts and four readability experts, while item validity and reliability were analyzed using the Rasch model. Results indicated a high content validity score (91%), confirming the questionnaire’s effectiveness in measuring students’ knowledge, attitudes, and behaviors. The item validity test showed all statement items were valid, and reliability analysis yielded strong internal consistency (Cronbach’s Alpha: 0.84 for person reliability and 0.85 for item reliability). These findings suggest that the questionnaire is a reliable instrument for assessing sustainability awareness. The study contributes to environmental education by providing a scientifically validated tool for measuring students’ understanding of sustainability, which can inform future curriculum development and policy-making efforts to enhance environmental awareness among students.